Multi-Stakeholder Engagement in Urban Sustainability - Fritz Akhmad Nuzir; Okta - Ainita; Kustiani - -; Aulia - Rahmawati; Aditya Mahatidanar Hidayat; Muhammad - Ardiansyah (Jurnal Arsitektur, 2026)
Multi-stakeholder engagement is an important approach in realizing urban sustainability, especially in the implementation of the United Nations Reports in the 2030 Agenda (Beisheim & Simon, 2015). Collaborative governance must support cross-sector participation in addressing the complexity of urban challenges together (Ansell & Gash, 2008)(Emerson et al., 2012). This study aims to analyze the practice of multistakeholder collaboration in sustainable urban development in Lampung Province and evaluate the shift of multi-stakeholder forums from dialogue to impactful action initiatives. This study also highlights good practices from local institutions that have consistently applied GEDSI principles in program planning and implementation. The research method used is a descriptive qualitative approach (case study). Lampung Province was chosen as the research location because it demonstrates quite active multistakeholder forum activity and has implemented sustainable development programs such as Communal Sanitation, Green and Independent Housing (H2M), and community initiatives in waste management (disperkim, 2024)(biroadpim.lampungprov.go.id, 2025)(Haluan, 2022).  The findings of this study include the transformation of collaborative action outputs between the Multi-stakeholder Forum, the role of government and local policy dynamics in the forum and data, collaboration between communities and the private sector, the application of GEDSI principles in development governance, and strengthening documentation and the role of the media. Suggestions for enhancing the multistakeholder forum encompass formal legalization, collective accountability, incorporations of GEDSI principles, and proactive engagement of the media, communities, and academics. The local government also contributes by offering continuous support to collaborator to guarantee contextual and inclusive solutions.